2022
DOI: 10.1155/2022/2987270
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Construction of Resource Ecological Compensation Mechanism Model under Rural Leisure Sports Environment

Abstract: In order to solve the problem of resource ecological compensation, this paper proposed a model of resource ecological compensation mechanism based on a rural leisure sports environment. The model is carried out in many places in China. The survey data involves 31 provinces, 10 years, and 43 indicators, with a total of 43 × 10 × 31 = 13,330 data. The preliminary basis of mechanism construction is summarized from four aspects. Finally, make full use of modern information technology to improve the network platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%